Doutor Martín de Azpilcueta Navarro: um estudo sobre a confissão e a educação na sociedade ibérica do século XVI - LIRA, Rafaela Franklin da Silva (2013)
This study aims to analyze the cultural, social and political Iberian trajectory of Martín de Azpilcueta Navarro in the sixteenth century. We seek to emphasize the studies around the religion’s and educational’s fields, in order to realize the new profile of the modern confession and the relation between Navarro and the Society of Jesus. Among the used sources we emphasize some Azpilcueta Navarro Martín’s manuals, especially the Manual Confessors & Penitents of 1560, letters written by the gownsman and by the priest Manuel da Nobrega, the Ecumenical Council of Trent and the Fourth Lateran Council. To build this work we analyzed the life story or biography. It is not intended here to present the own subject, through his life ( his (experiences, living spaces, etc.) the social and cultural practices of the Iberian Peninsula in the sixteenth century. We present connections between Martin de Azpilcueta Navarro and the Society of Jesus, this order was chosen by the Council of Trent to spread the faith and the Catholic doctrine among the heathen lands overseas. In the reforms’s context, the Navarro’s action in the disclosure if the new confession’s model through his classes and works, was very important in the formation of many Jesuit priests, especially Father Manuel da Nobrega, chief of the first Jesuit mission sent to America Portuguese in 1549. From the missionary work, the Catholic doctrine and religious practices were widespread on Earth Brasillis, which were developed in colonial society for centuries follwing.